Rekonstruksi Imaji Masa Kecil: Representasi Kelereng dalam Karya "The Marble Strike United Us" - Muhammad Abiyyu Army Fawwaz; Dyah Yuni Kurniawati (VisArt: Jurnal Seni Rupa dan Design, 2025)
Abstract: The creation of a painting with the theme of the traditional game of marbles as a form of reconstruction of childhood imagery full of social, cultural and aesthetic values. The game of marbles is not only represented as a recreational activity, but also as a symbol of collective memory and local identity that has begun to be marginalized by modern visual culture. With an explorative and reflective approach, this work combines contemporary illustrative visual elements and popular culture elements to deliver a communicative and emotional visual narrative. This research examines how the traditional game of marbles, as part of childhood experiences and local culture, is visually represented in the form of paintings. Using a qualitative method with a descriptive approach that focuses on the process of creating paintings based on childhood memories, especially through the traditional game of marbles. Through the depiction of expressions, gestures, and supporting visual elements, it succeeds in conveying a complex narrative that evokes the collective memory of the community towards traditional games as an important part of the childhood socialization process, as well as the novelty of concepts and techniques in an effort to emphasize the position of traditional games as a source of ideas for contemporary painting art creation.